The Growth of Root Rot Disease on Pepper Seed Applied by Trichoderma Harzianum Inoculum - S. Sofian; B. Hadisutrisno; A. Priyatmojo (Chemical Engineering Diponegoro University, 2013)
Root rot disease on pepper caused by Phytophthora capsici is one of the most important diseases on pepper. The using of antagonistic fungus of Trichoderma harzianum as a biological control agent of the pathogen is one of the important alternatives in controlling P. capsici without causing negative effects on the environment. The objectives of the research were to study about the ability of T. harzianum inoculum application in inhibiting the development of root-rot disease, influenced the growth of pepper seed, to studythe effective length time application of T. harzianum inoculum in inhibiting the development of root rot disease, and increased the growth of pepper seedlings. This research was arranged in a completely randomized design, with five treatments of length time application of T. harzianum inoculum i.e. control treatment without applicationtime of T. harzianum inoculum (K), application time of T. harzianum inoculum for 0 week (S0), application time of T. harzianum inoculum for 1 week (S1), application time of T. harzianum inoculum for two weeks (S2), application time of T. harzianum inoculum for three weeks (S3), and application time of T. harzianum inoculum for 4 weeks (S4) before planting. Each treatment was repeated15 times. The observed parameterswere disease percentage, the inhibition of antagonistic fungus, disease infection rate, plant height, number of leaves, wet and dry weight of plant, stem and leaves on pepper seed, and P. capsici population density. The result showed that application time of T. harzianum inoculumfor 4 weeks (S4) before planting is the most effective time in inhibiting the development of root rot disease than the other treatment sand also had significant effect on increasing the growth of pepper seed. The antagonism test showed that T. harzianum could inhibit P. capsiciin vitro. This result proves that application time of T. harzianum inoculums for 4 weeks (S4) before planting is more effective in inhibiting the development of root rot disease and able to increase the growth of pepper seedDoi: 10.12777/ijse.5.1.49-54 [How to cite this article: Sofian, B. Hadisutrisno, A. Priyatmojo. (2013). The Growth of Root Rot Disease on Pepper Seed Applied by Trichoderma Harzianum Inoculum. International Journal of Science and Engineering, 5(1):49-54. Doi: 10.12777/ijse.5.1.49-54 ]